Anti-inflammatory properties of S53P4 bioactive glass implant material. (December 2022) - Barrak, Fadi N.; Li, Siwei; Mohammed, Ali A.; Myant, Connor; Jones, Julian R.
Abstract: Objectives: To assess whether the dissolution products of S53P4 bioactive glass (BG) affect cellular response of macrophages and clinically relevant peri‑implant cell populations to dental implant particles in vitro . Cells chosen were human gingival fibroblasts (HGFs), osteoblasts and bone marrow derived stromal cells (HBMSCs). Methods: Melt-derived S53P4 bioactive glass were prepared. HGFs, Saos-2 human osteoblastic cell line, HBMSCs and macrophages, derived from THP-1 human monocytic cell line, were cultured in the presence of particles from commercially pure titanium (Ti-CP4), grade 5 titanium alloy (Ti-6Al-4V), titanium-zirconium alloy (Ti-15Zr) or zirconia (Zr) (with respective diameters of 34.1 ± 3.8, 33.3 ± 4.4, 97.8 ± 8.2 and 71.3 ± 6.1 µm) with or without S53P4 dissolution products (conditioned media contained 327.30 ± 2.01 ppm Ca, 51.34 ± 0.41 ppm P and 61.48 ± 1.17 ppm Si, pH 8.01 ± 0.21). Inflammatory and macrophage polarisation markers including TNF-ɑ, IL-1, IL-6 and CD206 were quantified using enzyme-linked immunosorbent assay (ELISA). Results: The presence of Ti-6Al-4V implant particles significantly induced the expression of pro-inflammatory markers in all tested cell types. S53P4 BG dissolution products regressed the particle induced up-regulation of pro-inflammatory markers and, appeared to suppress M1 macrophage polarisation. Conclusions: Implant particles, Ti-6Al-4V in particular, resulted in significant inflammatory responses from cells. S53P4 BG may possess anti-inflammatory properties and potentially mediate macrophage polarisation behaviour. Clinical Significance: The findings highlight that the use and benefits of BG is a promising field of study. Authors believe more collective efforts are required to fully understand the reliability, efficiency and exact mechanisms of action of BG in the search for new generation of treatment modalities in dentistry.